A phase 1b, randomized, double‐blind, placebo‐controlled, parallel cohort safety, tolerability, pharmacokinetics, pharmacodynamics and preliminary efficacy study of intravenously infused BIIB092 in patients with four different primary tauopathy syndromes. (31st December 2021) - Ljubenkov, Peter A.; Vandevrede, Lawren; Rojas, Julio C.; Tsai, Richard; Koestler, Mary; Graham, Danielle; Dam, Tien; Boxer, Adam L.
Abstract: Background: Aggregation of insoluble tau is a key autopsy finding in several neurodegenerative conditions including corticobasal syndrome (CBS), non‐fluent variant primary progressive aphasia (nfvPPA), frontotemporal lobar degeneration due to microtubule‐associated protein tau (MAPT) mutation, and traumatic encephalopathy syndrome (TES). Monoclonal‐antibody (mAb) therapies may promote clearance of pathogenic tau species, but differing protein isoforms and conformations may limit the affinity of mAbs for tau epitopes in distinct tauopathy syndromes. A "basket trial" allows for efficient investigation of drug target engagement in distinct diseases sharing common causative molecular alterations. We assessed the safety, tolerability, pharmacokinetic profile, and pharmacodynamic effects of BIIB092 (gosuranemab), a mAb targeting an N‐terminal tau epitope, in a basket trial enrolling participants with 4 different tauopathy syndromes: CBS, nfvPPA, symptomatic MAPT mutations, and TES. We also explored BIIB092's effects on CSF, MRI and clinical measures of disease severity. Method: N=25 participants were randomized approximately 3:1 to monthly intravenous infusions of 2000 mg BIIB092 (8 CBS, 4 nfvPPA, 4 MAPT, 2 TES) or placebo (CBS, 2 nfvPPA, 1 MAPT, 1 TES) for up to 6 months of double‐blind therapy. Subsequently 14 participants received monthly open label infusions for up to 6 months. Plasma, CSF, exploratory clinical measures, and volumetric imaging were collected at baseline, week 12, and week 24 of the double‐blind portion of the trial. Result: The study was terminated by Biogen in December 2019 (following negative results in a phase 2 in progressive supranuclear palsy), prior to completion of planned enrollment or treatment in recruited participants. Adverse events were more frequent in participants randomized to BIIB092 (83%) compared to placebo (28%), though no adverse events were attributed to study drug. In all patients randomized to BIIB092, we observed 90% reduction in detectable CSF N‐terminal tau epitopes at weeks 12 (mean ‐96.9%, SD 2.0) and 24 (mean ‐97.0%, SD 1.9) of the blinded treatment period. Analyses of other secondary and exploratory endpoints are underway. Conclusion: Six months of BIIB092 treatment was well tolerated and appears to bind to the N‐terminal epitopes in individuals with four different tauopathy syndromes.